Longitudinal dielectric relaxation in KD₂PO₄ under hydrostatic pressure - Levitskii, R.R.; Zachek, I.R.; Moina, A.P.; Duda, A.S. (Condensed Matter Physics, 2002)
Within the model proposed earlier, we study the effect of hydrostatic pressure
on relaxational dynamics of deuterated KD₂PO₄ type ferroelectrics.
Within the four particle approximation for deuteron ordering model and using
the Glauber approach, we calculate the longitudinal dynamic dielectric
permittivity of the strained crystal. Possible pressure dependences of the
permittivity and relaxation times are discussed В рамках запропонованої моделі досліджено вплив гідростатичного тиску на релаксаційну динаміку дейтерованих сегнетоелектриків типу KD₂PO₄. В наближенні чотиричастинкового кластера для моделі протонного впорядкування, в глауберівському підході розраховано поздовжню діелектричну динамічну проникність деформованого кристалу. Обговорюються можливі баричні залежності проникності та часів релаксації.